DESAIN TEMPAT PENGELOLAAN LIMBAH CANGKANG TERPADU (TPLCT) SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH LIMBAH PADAT RAJUNGAN - Anggraeni, Elisa; Rahayuningsih, Mulyorini; Nugraha, Bambang Arif; Amalia, Kiki Puspita; Fadhlurrakhman, Ariq Rizky; Alan, Jesslyn Alvina; Faidzin, Muhammad Nur (Jurnal Teknologi Industri Pertanian, 2023)
Blue swimming crab is a marine product commodity that has high economic value in Indonesia with a capacity of 47,895 kg/day, so there is a potential for shell waste of 25,187 kg/day distributed along Indonesia’s coastline. This shows that there is a high economic potential related to the increase in added value of crab shell waste. Shell waste is much needed by the fertilizer, chitin/chitosan and animal feed industries, but currently the quality of shell waste is not suitable and causes environmental pollution. This project was aimed at increasing the added value of crab shell waste which currently scattered, has various qualities and capacities, and need multi-stakeholder involvement. The solution developed was a collaborative business model in the form of TPLCT that has economic value, has a quality that is suitable for the shell processing industry, has an easy and efficient process, there is information transparency, and reduces environmental pollution. The prototype validation results show that the solution design provided is accepted by partners (APRI), stakeholders, and can answer existing problems. Based on the results of the study it can also be concluded that TPLCT is feasible from a financial perspective with criteria for NPV > 0 (Rp 201,257,103), IRR > BRI Retail SBDK (8.25%), namely 14.67%, B/C Ratio > 1 (1.3), and payback period < assuming a project age of 20 years (4.93 years). The selling price of dry shells increased for the shell, swimming legs, claws and other parts respectively Rp 1456/pcs, Rp 7573/kg, Rp 3786/kg, and Rp 2446/kg. Keywords: blue swimming crab shell, collaborative business model, agroindustry added values